PENDIDIKAN KRITIS REVOLUSIONER PETER MCLAREN DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM - Muhamad Agus Mushodiq (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2021)
This article aims to describe the relevance of Peter McLaren's revolutionary critical pedagogy and Islamic education through an ontological review. In conducting the analysis, the author uses a type of qualitative literature research with content analysis techniques. The results of this study are. First, Critical pedagogy and Islamic education emphasize practical approaches to teaching, learning, and research in teaching and learning activities. Second, the relevance of the revolutionary critical pedagogy goals of Islamic education lies in the social goals as a meeting point. Both have the goal of improving individuals (empower) and relationships between individuals socially. Third, in critical pedagogy, dialogue and dialectics are required between educators and students (both are subjects) so that the negotiation of knowledge for the construction of new knowledge can occur. Fourth, the alignment of the curriculum principles between revolutionary critical education and the principles of Islamic education is based on the principle voice conveyed by McLaren, so that students better understand the objectives of the material being taught.